Effect of cigarette smoke extract on inflammatory cytokine production and corticosteroid insensitivity in human airway smooth muscle cells - Alahmari, Mushabbab (2022)
Asthma is a chronic lung disease characterised by the presence of one or more respiratory symptoms, such as wheezing, chest tightness, breathlessness and coughing, which are attributed to airflow obstruction, airway hyperresponsiveness and airway inflammation. Airway inflammation in asthma is categorised into endotypes—namely Type 2 (T2, eosinophilic and T2-high) asthma, which has a good response to corticosteroid treatment, and non-Type 2 (non-T2, neutrophilic and T2-low) asthma, which has a poor response to corticosteroid treatment. Human airway smooth muscles (HASMCs) are crucial components of the airway structural wall because they display an inflammatory response by secreting cytokines and chemokines in response to inflammatory stimuli. Cigarette smoke (CS) is a known risk factor in developing airway inflammation, which can lead to asthma. Clinical studies have shown that asthmatic smokers tend to have low eosinophil counts and high neutrophil counts and display a poor response to corticosteroid therapy. But whether CS can modulate T2 and non-T2 inflammatory responses and induce corticosteroid insensitivity in vitro is largely unknown. It has been suggested that various mechanisms such as oxidative stress and cyclooxygenase-2 (COX-2) induction may play a key role in mediating the CS effect. However, the mechanisms underlying the proinflammatory effect of CS in asthma remain to be explored. We hypothesised that CS extract (CSE) may inhibit the production of T2 inflammatory cytokines (Th2 cytokines and eosinophil chemokines) and induce non-T2 inflammatory cytokines (IL-6, IL-8, and VEGF) in HASMCs via oxidative stress and COX-2 induction, thereby contributing to the development of corticosteroid-insensitive non-T2 endotype in asthma smokers.